2015
DOI: 10.1097/pas.0000000000000409
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Intra-alveolar Tumor Spread in Pulmonary Adenocarcinoma

Abstract: Tumor spread, in general, is the most important factor determining outcome in almost all malignant tumors. Lung tumors are unique with respect to potential routes for tumor dissemination, as apart from vascular, nodal, and distant spread of tumor cells, tumor spread through air spaces (STAS) might also occur. However, morphologic criteria for STAS and its prognostic impact have not been defined yet. We evaluated a series of 569 resected pulmonary adenocarcinomas (ADCs) for predefined morphologic criteria of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
264
4
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 225 publications
(293 citation statements)
references
References 22 publications
22
264
4
3
Order By: Relevance
“…In a series of 569 ADC STAS was significantly associated with male sex, lymph node and distant metastasis, tumor stage, and high-grade histological patterns (2). Further correlations were found with KRAS and BRAF mutations (2). Another recent study concerning STAS in a series of 318 stage I ADC confirmed and extended the yet available data.…”
Section: Correlation Of Stas With Clinicopathological Parameterssupporting
confidence: 69%
See 4 more Smart Citations
“…In a series of 569 ADC STAS was significantly associated with male sex, lymph node and distant metastasis, tumor stage, and high-grade histological patterns (2). Further correlations were found with KRAS and BRAF mutations (2). Another recent study concerning STAS in a series of 318 stage I ADC confirmed and extended the yet available data.…”
Section: Correlation Of Stas With Clinicopathological Parameterssupporting
confidence: 69%
“…In the second validation study, STAS was a significant prognosticator for both overall and disease-free survival even in patients with lobectomy and independent of the extent of STAS. Furthermore, STAS remained a worse prognosticator in multivariate analysis including the predominant pattern but not independent of stage (2). Although the analyzed subgroups were small, this study also demonstrated for the first time that the presence of STAS adds significant prognostic information to the predominant pattern (2), which was further underlined by a subsequent study focusing on the papillary pattern (16).…”
Section: Prognostic Impact Of Stassupporting
confidence: 56%
See 3 more Smart Citations